Visualization of the Nucleolus Using 5' Ethynyl Uridine - Dvořáčková, Martina; Fajkus, Jiří (Methods in molecular biology (Clifton, N.J.), 2023)
Labeling of the nucleolus in Arabidopsis thaliana can be achieved by incorporation of 5'-ethynyl uridine (EU) into bulk RNA. Although EU does not selectively label the nucleolus, the abundance of ribosomal transcripts results in the predominant accumulation of the signal in the nucleolus. Ethynyl uridine has the advantage of being detected via Click-iT chemistry providing a specific signal and low background. While the protocol presented here employs fluorescent dye and allows visualization of the nucleolus by microscopy, this method can also be used for other downstream applications. Though we tested nucleolar labeling only in A. thaliana, in principle it can be applied to other plant species.
Keywords: Click-iT; uridin; Uridine; Transcription; Nucleolus; Microscopy; Ethynyl Uridine; RNA; Cell Nucleolus; Confocal Microscopy; mikroskopie; Ribosomes; ribozomy; buněčné jadérko